Handbook of Materials Modeling 2018
DOI: 10.1007/978-3-319-42913-7_47-1
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Electronic Structure Calculations by Auxiliary-Field Quantum Monte Carlo

Abstract: The auxiliary-field quantum Monte Carlo (AFQMC) method provides a computational framework for solving the time-independent Schroedinger equation in atoms, molecules, solids, and a variety of model systems by stochastic sampling. We introduce the theory and formalism behind this framework, briefly discuss the key technical steps that turn it into an effective and practical computational method, present several illustrative results, and conclude with comments on the prospects of ab initio computation by this fra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…One is to allow the imposition of the constraints without incurring ergodicity problems 10,29,50 . The other is that, for groundstate or ZT calculations, it provides a clear and formal connection 28,51 with standard electronic structure methods within density-functional theory, which has enabled general computations in solids and molecular systems.…”
Section: Introductionmentioning
confidence: 99%
“…One is to allow the imposition of the constraints without incurring ergodicity problems 10,29,50 . The other is that, for groundstate or ZT calculations, it provides a clear and formal connection 28,51 with standard electronic structure methods within density-functional theory, which has enabled general computations in solids and molecular systems.…”
Section: Introductionmentioning
confidence: 99%
“…A very recent review of AFQMC and its applications also to excited states can be found in Ref. [96].…”
Section: Alternatives To Diffusion Monte Carlomentioning
confidence: 99%
“…Phaseless auxiliary-field quantum Monte Carlo (hereafter referred to as AFQMC) 52,53 is a systematically improvable stochastic electronic structure method which scales modestly with the fourth power of the system size in our current implementation. It has recently been shown to produce accurate triplet energies for all linear polyacenes with experimentally reported T1 energies (naphthalene through pentacene) as well as for biradicals.…”
Section: Introductionmentioning
confidence: 99%